INTEGRATED APPROACH TO ENERGY EFFICIENCY IN DESIGN AND CONSTRUCTION OF HOTEL AND RESTAURANT BUSINESS OBJECTS - Pogrebnyak, A. V.; Kucher, M. M.; Sabirov, O. V.; Grytsenko, A. V.; ZinchenkoH. К. (Systems and Technologies, 2024)
The article examines the impact of architectural solutions on the energy efficiency of hotel and restaurant business facilities. Particular attention is paid to the choice of materials, buildings orientation, constructive solutions, ventilation and lighting systems, and the integration of renewable energy sources. The analysis of modern architectural approaches that help reduce energy consumption and ensure the sustainability of the hotel and restaurant business is presented. The results of the study emphasize the importance of integrating energy-efficient technologies in the early stages of design and during the operation of buildings. The paper considers the main architectural aspects that affect the energy efficiency of hotels and restaurants and provides examples of modern solutions that allow for achieving high energy efficiency indicators. The purpose of this study is to investigate the impact of architectural solutions in the design and construction of hotel and restaurant business establishments on their energy efficiency. Based on this, its objectives are as follows: to characterize the impact of external factors of the location area of the establishment and its orientation relative to the cardinal points; to identify constructive opportunities to reduce heat loss; to analyze ventilation and air conditioning systems; to provide examples of the use of renewable energy sources; to prove the benefits of building management system automation; to determine the role of lighting system quality in improving energy efficiency; to analyze the use of environmentally friendly materials; to characterize modern energy-saving technologies and innovative materials; to analyze the impact of energy efficiency on business profitability. Investments in energy-efficient technologies are often perceived as additional costs that are not always a business priority. However, the long-term perspective shows the opposite: energy efficiency can have a significant impact on the profitability of hotels and restaurants. Energy-efficient buildings are becoming more attractive to guests who are increasingly paying attention to environmental aspects when choosing a place to stay or eat. The marketing advantage provided by energy efficiency certificates or participation in sustainability programs can be a significant factor in competing in the market. It is also worth noting that energy efficiency investments often have a short payback period. Due to reduced energy costs, such projects can pay off in 3-7 years, after which the company begins to receive a net profit from the saved funds.